2018
DOI: 10.1002/smll.201801348
|View full text |Cite
|
Sign up to set email alerts
|

Controlled, Low‐Temperature Nanogap Propagation in Graphene Using Femtosecond Laser Patterning

Abstract: Graphene nanogap systems are promising research tools for molecular electronics, memories, and nanodevices. Here, a way to control the propagation of nanogaps in monolayer graphene during electroburning is demonstrated. A tightly focused femtosecond laser beam is used to induce defects in graphene according to selected patterns. It is shown that, contrary to the pristine graphene devices where nanogap position and shape are uncontrolled, the nanogaps in prepatterned devices propagate along the defect line crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Maurice et al applied UDLW to initiate the formation of nanogap in graphene via electroburning, which is a promising tool for fabricating molecular electronic devices. [117] When the lateral sizes of the defect-free graphene regions reached 2-7 nm after fs-laser processing, the authors used a low bias voltage to guide defect formation in the layer (Figure 3d). UDLW helped to localize the defective areas and limit the extent of nanogap formation.…”
Section: Two-photon Oxidationmentioning
confidence: 99%
See 1 more Smart Citation
“…Maurice et al applied UDLW to initiate the formation of nanogap in graphene via electroburning, which is a promising tool for fabricating molecular electronic devices. [117] When the lateral sizes of the defect-free graphene regions reached 2-7 nm after fs-laser processing, the authors used a low bias voltage to guide defect formation in the layer (Figure 3d). UDLW helped to localize the defective areas and limit the extent of nanogap formation.…”
Section: Two-photon Oxidationmentioning
confidence: 99%
“…Reproduced with permission. [ 117 ] Copyright 2018, John Wiley and Sons. e) Near‐field distributions of a laser patterned “X” structure at an excitation wavelength of 9.588 µm and corresponding SEM image.…”
Section: Photochemical and Photophysical Effects In Ultrafast Laser P...mentioning
confidence: 99%
“…Studies on femtosecond laser patterning of graphene electrodes for thin-film transistors showed that the quality of the patterned electrodes was enhanced by ablation in vacuum conditions due to debris reduction [190]. Femtosecond laser ablation has been adopted by Maurice et al for obtaining nanogaps in monolayer graphene, opening a promising path for development of graphene-based nanogap systems for molecular electronics, memories and nanodevices [191]. Laser treatments performed under conditions slightly above the ablation threshold have been used for accurate laser-induced thinning of multilayer graphene, enabling precise control over the number of stacked sheets (up to single layers) [192,193].…”
Section: Treatments Based On Laser Ablationmentioning
confidence: 99%
“…[ 23 ] The absorption of laser energy occurs prior to lattice alterations, leading to a markedly non‐equilibrium state between electrons and lattices. [ 24 ] The superior characteristics enable the processing of lattice structures within a very brief timeframe and minimize thermal damage to the material, exhibiting excellent ablation controllability. [ 25 ] Guo [ 17 ] successfully achieved micron‐scale phase patterning from 1T/1T'‐MoS 2 to 2H‐MoS 2 utilizing the fs laser, affirming that the fs laser shortens the time by four orders of magnitude compared to CW irradiation.…”
Section: Introductionmentioning
confidence: 99%